Operation principles for hydrogen spark ignited direct injection engines for passenger car applications. (26th January 2022) - Fischer, Marcus; Sterlepper, Stefan; Pischinger, Stefan; Seibel, Jörg; Kramer, Ulrich; Lorenz, Thomas
Abstract: The sustainable reduction of greenhouse gas emissions from road transport requires solutions to achieve net-zero carbon dioxide emissions. Therefore, in addition to vehicles with electrified powertrains, such as those implemented in battery electric of fuel cell vehicles, internal combustion engines fueled with e-fuels or biofuels are also under discussion. An e-fuel that has come into focus recently, is hydrogen due to its potential to achieve zero tank-to-wheel and well-to-wheel carbon dioxide emissions when the electrolysis is powered by electricity from renewable sources. Due to the high laminar burning velocity, hydrogen has the potential for engine operation with high cylinder charge dilution by e.g. external exhaust gas recirculation or enleanment, resulting in increased efficiency. On the other hand, the high burning velocity and high adiabatic flame temperatures pose a challenge for engine cooling due to increased heat losses compared to conventional fuels. To further evaluate the use of hydrogen for small passenger car engines, a series production 1 L 3 cylinder gasoline engine provided by Ford Werke GmbH was modified for hydrogen direct injection. The engine was equipped with a high pressure external exhaust gas recirculation system to investigate charge dilution at stoichiometric operation. Due to limitations of the turbocharging system, very lean operation, which can achieve nitrogen oxides raw emissions below 10 ppm, was limited to part load operation below BMEP = 8 bar. Thus, a reduction of the nitrogen oxides emission level at high loads compared to stoichiometric operation was not possible. At stoichiometric operation with external exhaust gas recirculation engine efficiency can be increased significantly. The comparison of stoichiometric hydrogen and gasoline operation shows a reduced indicated efficiency with hydrogen with significant faster combustion of hydrogen at comparable centers of combustion. However, higher boost pressures would allow to achieve even higher indicated efficiencies by charge dilution compared to gasoline engine operation. Highlights: Hydrogen direct injection investigated at series production gasoline engine. Reduced indicated efficiency compared to gasoline at stoichiometric operation. Charge dilution shows significant potential to increase the indicated efficiency. Enleanment can achieve near zero raw emission engine operation. Near zero raw emission engine operation was limited to low part load operation.